Long range neutrino forces in the cosmic relic neutrino background - Ferrer, F.; Grifols, J. A.; Nowakowski, M. [UNESP] (American Physical Society (APS), 2000)
Neutrinos mediate long range forces among macroscopic bodies in a vacuum. When the bodies are placed in the neutrino cosmic background, these forces are modified. Indeed, at distances long compared to the scale T -1, the relic neutrinos completely screen off the two-neutrino exchange force, whereas for small distances the interaction remains unaffected. ©2000 The American Physical Society.